Inhibition of N-acylethanolamine acid amidase reduces nicotine-induced dopamine activation and reward. (January 2019) - Sagheddu, Claudia; Scherma, Maria; Congiu, Mauro; Fadda, Paola; Carta, Gianfranca; Banni, Sebastiano; Wood, JodiAnne T.; Makriyannis, Alexandros; Malamas, Michael S.; Pistis, Marco
Abstract: Tobacco smoke is the leading preventable cause of death in the world and treatments aimed to increase success rate in smoking cessation by reducing nicotine dependence are sought. Activation of peroxisome proliferator-activated receptor-alpha (PPARα) by synthetic or endogenous agonists was shown to suppress nicotine-induced activation of mesolimbic dopamine system, one of the major neurobiological substrates of nicotine dependence, and nicotine-seeking behavior in rats and monkeys. An alternative indirect way to activate PPARα is inhibition of N-acylethanolamine acid amidase (NAAA), one of the major hydrolyzing enzyme for its endogenous agonists palmitoylethanolamide (PEA) and oleoylethanolamide (OEA). We synthetized a novel specific brain permeable NAAA inhibitor, AM11095. We administered AM11095 to rats and carried out brain lipid analysis, a functional observational battery (FOB) to assess toxicity, in vivo electrophysiological recording from dopamine cells in the ventral tegmental area, brain microdialysis in the nucleus accumbens shell and behavioral experiments to assess its effect on nicotine -induced conditioned place preference (CPP). AM11095 (5 and 25 mg/kg, i.p.) was devoid of neurotoxic and behavioral effects and did not affect motor behavior and coordination. This NAAA inhibitor (5 mg/kg i.p.) increased OEA and PEA levels in the hippocampus and cortex, prevented nicotine-induced activation of mesolimbic dopamine neurons in the ventral tegmental area, nicotine-induced elevation of dopamine levels in the nucleus accumbens shell and decreased the expression of nicotine CPP. Our results indicate that NAAA inhibitors represent a new class of pharmacological tools to modulate brain PEA/PPARα signalling and show potential in the treatment of nicotine dependence. Highlights: We synthetized the novel specific brain permeable NAAA inhibitor AM11095. Lipid analysis showed that AM11095 increased levels of PPARα endogenous ligands in discrete rat brain areas. AM11095 prevented nicotine-induced increase in dopamine transmission in rats. AM11095 decreased the expression of nicotine conditioned place preference in rats.